FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TERJADINYA KECELAKAAN KERJA PADA PEKERJA PROYEK PEMBANGUNAN GEDUNG DI PT. X TAHUN 2020 - Nikhmatul Huda; Azizah Musliha Fitri; Arga Buntara; Dyah Utari (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
The construction sector is ranked first as the most dangerous occupation in the world and is an area with a high risk of occupational accidents. According to BPJS Ketenagakerjaan data in 2019, cases of work accidents in Indonesia 2017 increased in 2018. The purpose of this study was to determine the relationship between age, OHS knowledge, OHS supervision, unsafe act, and unsafe condition for building construction project workers at PT. X. This research was quantitative study with a cross-sectional study design. The sampling technique used simple random sampling where the sample amounted to 109 workers. The results of the research analysis using the chi-square statistical test showed that the variables of age (p-value = 0,662), OHS knowledge (p-value 0,003), OHS supervision (p-value 0,001), unsafe act (p-value 0,002), unsafe condition (p-value 0,000) with a significance limit of α = 0,05. It can be concluded that there is an associated between OHS knowledge, OHS supervision, unsafe act, and unsafe condition with work accidents and there is no associated between age with work accidents. It is recommended that companies provide education to workers in the form of providing OHS knowledge through the toolbox meeting program and periodically monitoring of conditions in the work field.